Protocol for process evaluation of SMART Mental Health cluster randomised control trial: an intervention for management of common mental disorders in India - Anushka Patel; David Peiris; Pallab K Maulik; Graham Thornicroft; Shekhar Saxena; Sudha Kallakuri; Amanpreet Kaur; Siddhardha Devarapalli; Mercian Daniel; Beverley M Essue; Shashi Kant; D Praveen; et al. (BMJ Open)
Introduction In India about 95% of individuals who need treatment for common mental disorders like depression, stress and anxiety and substance use are unable to access care. Stigma associated with help seeking and lack of trained mental health professionals are important barriers in accessing mental healthcare. Systematic Medical Appraisal, Referral and Treatment (SMART) Mental Health integrates a community-level stigma reduction campaign and task sharing with the help of a mobile-enabled electronic decision support system (EDSS)—to reduce psychiatric morbidity due to stress, depression and self-harm in high-risk individuals. This paper presents and discusses the protocol for process evaluation of SMART Mental Health.Methods and analysis The process evaluation will use mixed quantitative and qualitative methods to evaluate implementation fidelity and identify facilitators of and barriers to implementation of the intervention. Case studies of six intervention and two control clusters will be used. Quantitative data sources will include usage analytics extracted from the mHealth platform for the trial. Qualitative data sources will include focus group discussions and interviews with recruited participants, primary health centre doctors, community health workers (Accredited Social Health Activits) who participated in the project and local community leaders. The design and analysis will be guided by Medical Research Council framework for process evaluations, the Reach, Effectiveness, Adoption, Implementation and Maintenance (RE-AIM) framework, and the normalisation process theory.Ethics and dissemination The study has been approved by the ethics committee of the George Institute for Global Health, India and the Institutional Ethics Committee, All India Institute of Medical Sciences (AIIMS), New Delhi. Findings of the study will be disseminated through peer-reviewed publications, stakeholder meetings, digital and social media platforms.Trial registration number CTRI/2018/08/015355.